The Surety Conundrum - Jones, H (Mine Closure 2006: Proceedings of the First International Seminar on Mine Closure, 2006)
The paper outlines the requirement for financial sureties to cover the costs of mine closure from the perspective of various stakeholders, in particular government regulators, mining companies, financial organisations and the communities affected by the mining operations. It describes the development of the Western Australian system of Unconditional Performance Bands. Methods of calculating closure costs, including a risk based approach are outlined showing the sometimes conflicting methods used by operators, governments and financial organisations respectively. The pros and cons of these methods are discussed together with the requirement for ‘after care’, salvage values and asset transfer to local communities. The various types of financial sureties are discussed from the point of view of meeting the requirements of the various stakeholders and the direct and indirect impacts on those stakeholders. The large sum of money tied in financial sureties is effectively money removed from the mining industry and some implications of this are outlined. The ‘double charge’ of government financial surety requirements and corporate internal provisioning is addressed and several potential methods of resolving this are outlined.